Non-antibiotic therapies in uncomplicated lower urinary tract infections. Recommendations of the Polish Society of Family Medicine - Babicki, Mateusz; Kiliś-Pstrusińska, Katarzyna; Kołodziej, Anna; Mastalerz-Migas, Agnieszka; Miotła, Paweł (Lekarz POZ, 2024)
Urinary tract infections (UTIs) are among the most common bacterial infectious diseases. They are characterised by a tendency to recur. Antibiotics or chemotherapeutic agents are most commonly used in the treatment of UTIs. Given the increasing antibiotic resistance of uropathogenic bacteria, it is necessary to rationalise their use and consider non-antibiotic treatments, particularly phytotherapy, and to carry out preventive measures. This paper discusses non-antibiotic therapies for lower urinary tract infections, paying particular attention to the scientific evidence on their efficacy. Non-antibiotic therapies that can be used in pregnant women with UTIs are presented separately. Their effectiveness in postmenopausal women was also analysed. The issue of so-called asymptomatic bacteriuria, i.e. bacterial growth in the urine of a person without clinical symptoms of UTIs, was discussed. Asymptomatic bacteriuria does not require treatment except in certain situations. Inappropriate antibiotic therapy places an unnecessary burden on the patient and promotes antibiotic resistance of bacteria.